De Novo Macrocyclic Peptide Inhibitors of Hepatitis B Virus Cellular Entry. Issue 7 (19th July 2018) - Passioura, Toby; Watashi, Koichi; Fukano, Kento; Shimura, Satomi; Saso, Wakana; Morishita, Ryo; Ogasawara, Yuki; Tanaka, Yasuhito; Mizokami, Masashi; Sureau, Camille; Suga, Hiroaki; Wakita, Takaji
Summary: Hepatitis B virus (HBV) constitutes a significant public health burden, and currently available treatment options are not generally curative, necessitating the development of new therapeutics. Here we have applied random non-standard peptide integrated discovery (RaPID) screening to identify small macrocyclic peptide inhibitors of HBV entry that target the cell-surface receptor for HBV, sodium taurocholate cotransporting polypeptide (NTCP). In addition to their anti-HBV activity, these molecules also inhibit cellular entry by the related hepatitis D virus (HDV), and are active against diverse strains of HBV (including clinically relevant nucleos(t)ide analog-resistant and vaccine escaping strains). Importantly,  these macrocyclic peptides, in contrast to other NTCP-binding HBV entry inhibitors, exhibited no inhibition of NTCP-mediated bile acid uptake, making them appealing candidates for therapeutic development. Graphical Abstract: Highlights: Identification of multiple macrocyclic peptide inhibitors of HBV (and HDV) entry Pan-genotypic anti-viral activity No effect on endogenous function of the HBV cellular receptor NTCP Abstract : Hepatitis B virus infection causes serious illness and current treatments are not curative. In this work, Passioura et al. describe diverse small macrocyclic peptides that bind to the cellular receptor for HBV, sodium taurocholate cotransporting polypeptide (NTCP), and block viral entry without affecting NTCP's taurocholate transporting activity.